Evaluation, challenges, and countermeasures of current domestic COVID-19 vaccines - SHI Ziwei; HUANG Jiao; WEI Sheng (Yixue xinzhi zazhi)
Since the outbreak of COVID-19, China has been leading the world in vaccines research, providing a powerful tool for epidemic prevention. The domestic COVID-19 vaccine displays acceptable and efficient protection and safety in clinical trials and real world research. However, there are still many challenges for domestic vaccines due to uncertainty about the duration of protection and effec-tiveness against multiple variant strains. Using a homologous vaccine to enhance immunity is feasible to deal with the immediate situation, however, in the long run, it is necessary to speed up the development of multivalent and universal vaccines for COVID-19. At the same time scientific and standardized safety monitoring is necessary as a priority so as to accurately assess the long-term safety of domestic vaccines.